3-min all-out effort on cycle ergometer is valid to estimate the anaerobic capacity by measurement of blood lactate and excess post-exercise oxygen consumption - Zagatto, Alessandro Moura [UNESP]; Redkva, Paulo Eduardo [UNESP]; de Poli, Rodrigo Araújo Bonetti [UNESP]; González, Joel Abraham Martinez [UNESP]; Brandani, Jeniffer Zanetti [UNESP]; Penedo, Thiago [UNESP]; Bertuzzi, Rômulo Cássio De Moraes (Wiley, 2019)
The purpose of this study was to investigate the use of a single 3-min all-out maximal effort to estimate anaerobic capacity (AC) through the lactate and excess post-exercise oxygen consumption (EPOC) response methods (AC [La − ]+EPOCfast ) on a cycle ergometer. Eleven physically active men (age = 28.1 ± 4.0 yrs, height = 175.1 ± 4.2 cm, body mass = 74.8 ± 11.9 kg and ⩒O 2max = 40.7 ± 7.3 mL kg −1 min −1 ), participated in the study and performed: i) five submaximal efforts, ii) a supramaximal effort at 115% of intensity of ⩒O 2max, and iii) a 3-min all-out maximal effort. Anaerobic capacity was estimated using the supramaximal effort through conventional maximal accumulated oxygen deficit (MAOD) and also through the sum of oxygen equivalents from the glycolytic (fast component of excess post-exercise oxygen consumption) and phosphagen pathways (blood lactate accumulation) (AC [La − ]+EPOCfast ), while during the 3-min all-out maximal effort the anaerobic capacity was estimated using the AC [La − ]+EPOCfast procedure. There were no significant differences between the three methods (p > 0.05). Additionally, the anaerobic capacity estimated during the 3-min all-out effort was significantly correlated with the MAOD (r = 0.74; p = 0.009) and AC [La − ]+EPOCfast methods (r = 0.65; p = 0.029). Therefore, it is possible to conclude that the 3-min all-out effort is valid to estimate anaerobic capacity in physically active men during a single cycle ergometer effort.
Keywords: all-out efforts; Anaerobic capacity; cycle exercise; excess post-exercise oxygen consumption; maximal accumulated oxygen deficit